2000
DOI: 10.1159/000053988
|View full text |Cite
|
Sign up to set email alerts
|

Update on Antiviral DNA Vaccine Research (1998–2000)

Abstract: DNA vaccines can induce protective cellular and humoral immune responses and have therefore been used during the last decade to develop vaccines against a variety of different pathogens. Because current antiviral vaccines predominantly generate humoral immunity, DNA immunization may be especially useful to provide long-term protection against viral diseases that also require cellular immunity (e.g. HIV). A significant number of articles published in the field of DNA vaccines are dealing with viral diseases, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 159 publications
1
8
0
1
Order By: Relevance
“…One of the study conducted on mice with intra-cerebral inoculation of DENV2 showed protection owing to chimeric DNA vaccine. Similar results of chimeric DNA vaccines were observed in rhesus macaques [69]. Chimeric DNA vaccine with booster dose regimen has been tested against several deadly pathogens including DENV.…”
Section: Chimeric Dna Vaccinessupporting
confidence: 66%
“…One of the study conducted on mice with intra-cerebral inoculation of DENV2 showed protection owing to chimeric DNA vaccine. Similar results of chimeric DNA vaccines were observed in rhesus macaques [69]. Chimeric DNA vaccine with booster dose regimen has been tested against several deadly pathogens including DENV.…”
Section: Chimeric Dna Vaccinessupporting
confidence: 66%
“…However, an effective vaccine is not available and will remain unattainable for the next decade on account of the heterogeneity of the virus groups and subtypes. A DNA vaccine has likewise so far failed to make any headway in humans in terms of generating post-vaccination immunity to prevent the transmission of HIV infection [46,47]. The only options for limiting the spread of HIV for the time being are therefore promotion of awareness of routes of transmission and use of appropriate preventive measures.…”
Section: Epidemiologymentioning
confidence: 99%
“…Ein wirksamer Impfstoff steht nicht zur Verfügung und wird wegen der Heterogenität der Virus-Gruppen und Subtypen auch innerhalb der nächsten Dekade nicht hergestellt werden können. Auch eine DNA-Vakzine hat bisher im Menschen keinen Durchbruch zur Generierung einer postvakzinalen Immunität zur Verhinderung der HIV-Infektionsübertragung gebracht [46,47]. Daher sind Aufklärung über die Übertragungs-wege und Anwendung geeigneter Prä-ventionsmaßnahmen momentan die einzige Interventionsmöglichkeit.…”
Section: Epidemiologieunclassified